A acessibilidade pelas abordagens da arquitetura e da terapia ocupacional: sombreamento versus cooperação inter-disciplinar para a inclusão social - Cristiane Luisa Renger (2009)
This study aims at analyzing the development of professional performance in the fields of Architecture and Occupational Therapy. It includes a content analysis for comparison of course program syllabus of these two professional careers. In addition, the study explores the potential application of data gathering instruments about performance evaluation of person-environment fit. These instruments were created in each one of these professional fields. The goal is to evidence that the emphasis of each professional approach occurs in opposing directions. On one hand, Architects focus on addressing spatial structures of the built environment in order to provide user satisfaction. On the other hand, Occupational Therapists approach human abilities in order to study and environmental adaptations and behavioral adjustments that may extend functional performance. Therefore, there is great potential of mutual contribution between these two professions for knowledge growth about the person-environment relations. However, gaps in learning processes generate distortions for inter-disciplinarity contributions. Consequently, professional activities in one field over shadowed the other in terms of opportunities and responsibilities, as much that occupational therapists explore the technical standards of accessibility whereas architects develop design projects without a response to diversity of users´ functional abilities. Adopting case studies, this research study finds evidence that Architects and occupational therapists approached suggested problems with similar understanding, by crossing the borders of professional activities and abilities. The contribution of this study lays on reflective thinking about development and application of technical instruments in each profession, which must structure professional activities and enhances cooperation, information exchange and allows the multi-disciplinary teamworks for inclusive applications of universal design.